THE EFFECT OF VIRTUAL LITERATURE CIRCLE ON UNIVERSITY STUDENTS’ READING COMPREHENSION: A GENDER-BASED ANALYSIS - Mutiara Ayu; Zelvia Liska Afriani; Dyah Aminatun (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
This study investigates the effect of Virtual Literature Circles (VLCs) on the reading comprehension of university students, with a focus on gender-based differences. A mixed-methods approach was employed, involving a quasi-experimental design with pre-and post-tests, questionnaires, and interviews. The participants were divided into an experimental group (n = 30) and a control group (n = 30). The mean post-test score of the experimental group increased significantly from 65.23 (SD = 6.89) to 82.47 (SD = 5.32), while the control group showed a smaller improvement from 64.87 (SD = 7.14) to 70.23 (SD = 6.75). Independent sample t-tests confirmed a statistically significant difference in post-test scores between the two groups (p < 0.01). Gender-based analysis revealed that female students in the experimental group outperformed male students, with mean post-test scores of 84.15 (SD = 4.87) and 80.32 (SD = 5.64), respectively. Questionnaire and interview data indicated that female students reported higher levels of engagement, confidence, and perceived benefit from the VLCs. The findings suggest that VLCs are an effective and gender-responsive strategy for improving reading comprehension in higher education, particularly in virtual learning contexts.